Study of cucumber accessions from the VIR collection for their agronomic traits in the Lower Volga Region - E. H. Sukhanberdina; A. A. Grushin; T. M. Piskunova (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. One of the global problems presently faced by humanity is obesity and overweight. For treatment and prevention of this disease, doctors recommend consuming more vegetables, cucumbers in particular. Despite the fact that Russia is one of the major cucumber producers, its average yield is more than twice lower than in the EU countries. To meet the demand of the population, it is necessary to additionally import the missing products. In this regard, the urgent need for an increase of cucumber production is obvious, and first of all, by raising the yield.Materials and methods. The research was conducted at the experimental sites of Volgograd Experiment Station of VIR. Accessions from VIR’s cucumber collection served as the material for the study. Methods developed and accepted by VIR were used in the research.Results and conclusions. Such agronomic characteristics as yield, fruit weight and length, thorn color, dry matter and sugar content were studied. A noticeable direct correlation was found between fruit length and fruit weight, and moderate direct correlations were observed between yield and fruit length, yield and fruit weight, dry matter and sugars. The indicators showing suitability of accessions for salting and canning were analyzed. Accessions that can be used in breeding practice are recommended. A conclusion is made about the prospects of breeding for valuable agronomic traits using long-fruited forms of cucumber from the countries of South-East Asia and the Russian Far East.